Synthesis of Aryl-bis(3-methyl-1-phenyl-5-pyrazolone-4-yl)methane in Water - Wang, Ai-Qing; Jin, Tong-Shou; Cheng, Zhao-Li; Li, Tong-Shuang (Asian Journal of Chemistry, 2010)
A synthesis of aryl-bis(3-methyl-1-phenyl-5-pyrazolone-4-yl)methane from aromatic aldehyde and 3-methyl-1-phenyl-5-pyrazolin-5-one catalyzed by hexadecyltrimethyl-ammonium bromide in water is described. This method provides several advantages such as high yield, simple workup procedure and environment friendly.